Plasma redox and inflammatory patterns during major depressive episodes: a cross-sectional investigation in elderly patients with mood disorders. (19th August 2021) - Carpita, Barbara; Betti, Laura; Palego, Lionella; Bartolommei, Natalia; Chico, Lucia; Pasquali, Livia; Siciliano, Gabriele; Monzani, Fabio; Franchi, Riccardo; Rogani, Sara; Mucci, Federico; Elefante, Camilla; et al.
Abstract: Background: While both depression and aging have been associated with oxidative stress and impaired immune response, little is known about redox patterns in elderly depressed subjects. This study investigates the relationship between redox/inflammatory patterns and depression in a sample of elderly adults. Methods: The plasma levels of the advanced products of protein oxidation (AOPP), catalase (CAT), ferric reducing antioxidant power (FRAP), glutathione transferase (GST), interleukin 6 (IL-6), superoxide dismutase (SOD), total thiols (TT), and uric acid (UA) were evaluated in 30 patients with mood disorders with a current depressive episode (depressed patients, DP) as well as in 30 healthy controls (HC) aged 65 years and over. Subjects were assessed with the Hamilton Depression Rating Scale (HAM-D), the Hamilton Rating Scale for Anxiety (HAM-A), the Geriatric Depression Rating Scale (GDS), the Scale for Suicide Ideation (SSI), the Reason for Living Inventory (RFL), the Activities of Daily Living (ADL), and the Instrumental Activity of Daily Living (IADL). Results: DP showed higher levels than HC of AOPP and IL-6, while displaying lower levels of FRAP, TT, and CAT. In the DP group, specific correlations were found among biochemical parameters. SOD, FRAP, UA, and TT levels were also significantly related to psychometric scale scores. Conclusion: Specific alterations of redox systems are detectable among elderly DP.